SUPERVISI AKADEMIK PENGAWAS GURU PAI PADA MADRASAH DI KOTA BENGKULU - Minarni Minarni (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2019)
The purpose of this update is to analyze the academic supervision of PAI teacher supervisors in the madrasa in the city of Bengkulu. This study discusses the supporting factors of the academic supervision of madrasah teacher supervisors in Bengkulu City, where schools and religious teachers always receive the arrival of supervisors and the distance to the school location is classified as accessible because they are in the city. While the inhibiting factors of academic supervision are caused by supervisors not mastering academic supervision techniques and rarely getting supervisory training. To overcome the above problems, the solution is done so that the academic supervision of madrasah teacher supervisors can be more effective in improving the competence of madrasah professional teachers are: recruitment and appointment of new supervisors by the Ministry of Religion, supervisors need to conduct more intensive academic supervision, improve guidance for supervisors through monitoring and evaluating the planning and implementation of programs carried out by supervisors on a regular basis and need to be implemented in a systematic manner and clear penalties and programmed with routine activities that can uphold the improvement of supervisory competence, which is related to the support of academic supervisors.